(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2025)
In the wake of the incursion by Hamas militants into Israel in the early hours of 7 October, a deluge of disinformation in the form of videos and photographs purporting to depict the conflict has inundated various social media platforms, thereby creating a significant challenge for global observers attempting to differentiate between actual occurrences and fictionalised representations. Fake news often appeals to emotions and instincts. During periods of war, strife and disagreement, it is common for misinformation and counterfeit news to circulate with great speed and ease, prompted by escalated sentiments and a lack of certainty. Journalists, governmental bodies, individuals, and organisations circulated inaccurate and misleading information for various reasons, including spreading propaganda, manipulating public opinion, or provoking discord. The paper aims to study the impact of fake news and deepfakes during the Israel and Hamas conflict in 2023 and discuss India’s stance in the ongoing war. The paper aims to analyse the reason behind misinformation in the ongoing war, understand how media literacy can help debunk fake news and learn techniques to approach online misinformation during a conflict. The researchers have adopted framing analysis and thematic analysis to identify and analyse the fake news identified by two fact-checkers in India. Digital media literacy is an effective solution to fight against misinformation, especially during a global crisis.